The Influence of TripAdvisor Reviews and Social Media Marketing Through Instagram on Brand Image at InterContinental Bali Sanur Resort - Sugiarta, Komang Rikha (Formosa Journal of Applied Sciences, 2024)
The objective of this research is to understand how the brand image of InterContinental Bali Sanur Resort is influenced by TripAdvisor reviews and Instagram social media marketing. The study aims to serve as a reference and evaluation material for the management of InterContinental Bali Sanur Resort to raise awareness about its brand image. The research uses questionnaires and documentation studies as data collection methods, with the study taking approximately four months to complete. One hundred respondents participated in the survey, which was distributed via Google Forms. The findings indicate that the brand image of InterContinental Bali Sanur Resort is positively and significantly influenced, both partially and simultaneously, by social media marketing on Instagram and TripAdvisor reviews.